The multidimensional generalization of Bauer’s g-algorithm - Dmytryshyn, R.I. (Carpathian Mathematical Publications, 2012)
The algorithm for the expansion of the given formal multiple power series into the corresponding multidimensional g-fraction with independent variables is constructed and the conditions of existence of such algorithm are established.